LFA-1 on leukemic cells as a target for therapy or drug delivery - Phongpradist R. (2014)
Leukemia therapeutics are aiming for improved efficacy by targeting molecular markers differentially expressed on cancerous cells. Lymphocyte function-associated antigen-1 (LFA-1) expression on various types of leukemia has been well studied. Here, the role and expression of LFA-1 on leukemic cells and the possibility of using this integrin as a target for drug delivery is reviewed. To support this rationale, experimental results were also included where cIBR, a cyclic peptide derived from a binding site of LFA-1, was conjugated to the surface of polymeric nanoparticles and used as a targeting ligand. These studies revealed a correlation of LFA-1 expression level on leukemic cell lines and binding and internalization of cIBR-NPs suggesting a differential binding and internalization of cIBR-NPs to leukemic cells overexpressing LFA-1. Nanoparticles conjugated with a cyclic peptide against an accessible molecular marker of disease hold promise as a selective drug delivery system for leukemia treatment. © 2010 Bentham Science Publishers Ltd.